Rubus violaceifrons (Rosaceae), a new bramble species from Bohemia (Central Europe, Czech Republic) - Havlíček, Petr; Trávníček, Bohumil; Velebil, Jiří (Phytotaxa, 2022)
Rubus violaceifrons, a new species from central and north-eastern Bohemia (Czech Republic) is described and illustrated, and its distribution is characterized in detail. We classify it as a member of the series Pallidi of the subgenus Rubus, section Rubus and subsection Hiemales, although its weak specimens partly resemble R. guentheri from ser. Glandulosi. Like all species of R. ser. Pallidi studied so far, R. violaceifrons is tetraploid, as determined using flow cytometry. A detailed morphological comparison of the new bramble species with similar taxa is presented. A determination key including all taxa of the R. ser. Pallidi occurring in the Czech Republic is provided.